Effect of Deuterium Content on the Optical Properties of DKDP Crystals. Issue 6 (15th March 2018) - Xu, Mingxia; Zhang, Lisong; Liu, Fafu; Wang, Shaoyan; Lian, Yafei; Wang, Fang; Wang, Zhengping; Xu, Xinguang; Sun, Xun; Sun, Shaotao
Abstract: In this paper, the optical properties of deuterated potassium dihydrogen phosphate (DKDP) crystals with deuterium content of 55, 65 and 70% grown by traditional temperature‐reduction method are studied, including weak absorption, non‐uniformities of refractive indices, 3ω conversion efficiency and the 3ω laser damage threshold (3ω LDT). The results indicate that the weak absorption of 70% DKDP crystal is smaller than that of 55 and 65% DKDP. The result of non‐uniformities of refractive indices is further confirmed that the variation of deuterium content has little effect on the homogeneity of DKDP crystals. The 3ω conversion efficiency is measured under the optimum phase matching angle and 3ω conversion efficiency of 70% DKDP crystal is the highest, which achieved 50%. The results indicate that 3ω LDT of 70% DKDP crystal is slightly higher than that of 55 and 65% DKDP. Abstract : In this paper, the optical properties of DKDP crystals with deuterium content of 55, 65 and 70% grown by traditional temperature‐reduction method are studied, including weak absorption, non‐uniformities of refractive indices, 3ω conversion efficiency and the 3ω laser damage threshold (3ω LDT). 70% DKDP crystal has the best optical performance.